Environmental vulnerability, age and the promises of anti‐age discrimination law. Issue 2 (25th February 2019) - Kaya, Refia
Abstract : Discussions on equality between age groups and the practice of anti‐age discrimination law often tend to focus on the rights of the elderly on the labour market. This article is motivated by the current climate change cases, which emphasize broader age inequalities. It aims to highlight the unexplored potential of anti‐age discrimination law. Moreover, it explores the possible added value of this law when other legal ways to defend environmental rights are considered. Anti‐age discrimination law could thus offer a meaningful and effective ground to address age‐related environmental vulnerabilities.